2013
DOI: 10.1051/0004-6361/201321042
|View full text |Cite
|
Sign up to set email alerts
|

3D climate modeling of close-in land planets: Circulation patterns, climate moist bistability, and habitability

Abstract: The inner edge of the classical habitable zone is often defined by the critical flux needed to trigger the runaway greenhouse instability. This 1D notion of a critical flux, however, may not be all that relevant for inhomogeneously irradiated planets, or when the water content is limited (land planets). Based on results from our 3D global climate model, we present general features of the climate and large-scale circulation on close-in terrestrial planets. We find that the circulation pattern can shift from sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
329
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(346 citation statements)
references
References 69 publications
13
329
2
2
Order By: Relevance
“…To really assess the possibility of water stability at the surface, inclusion of the water cycle, as in Leconte et al (2013), is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…To really assess the possibility of water stability at the surface, inclusion of the water cycle, as in Leconte et al (2013), is mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…We adopted the same temperature grids as in Leconte et al (2013) with values T = {110, 170, ..., 710} K and the same pressure grids with values p = {10 −3 ,10 −2 ,...,10 5 } mbar. The water volume mixing ratio could vary between 10 −7 to 1.…”
Section: Model Parametersmentioning
confidence: 99%
“…The bigger they are, the lower the albedo. In our model, the cloud ice particles have a size that varies depending on the water mixing ratio (see Leconte et al 2013 for details). In Yang et al (2013) the size is not indicated, but is said to be the same size as observed on Earth.…”
Section: Circular Orbitsmentioning
confidence: 99%
See 2 more Smart Citations